Life Cycle Assessment Pada Pembibitan Kelapa Sawit Untuk Menghitung Emisi Gas Rumah Kaca - Hisyam Musthafa Al Hakim; Wahyu Supartono; Agustinus Suryandono (Pusat Publikasi Jurnal Universitas Islam Kalimantan, 2014)
Palm oil plantations in Indonesia is growing every year due to increased consumption of vegetable oil in line with the increase in the population of the world that are used as food , cosmetics , renewable sources , etc. Challenges in the development of palm oil plantations are problems and negative issues; land conflicts, damage to biodiversity, and environmental damage issues. Environmental damage caused by palm oil plantations became the object of attack developed countries and Non Governmental Organization (NGO), with the pretext to cause an increase in Greenhouse Gas (GHG) emissions that cause global warming. This research aimed to determine the Greenhouse Gas (GHG) emissions in palm oil seedling production. Methods carried out were studying the environmental aspects of a product by Life Cycle Assessment (LCA) in which all environmental aspects were analyzed and evaluated throughout its life cycle. Steps in LCA were goal and scope definition, life cycle inventory, life cycle impact assessment, and life cycle interpretation. The result showed that in the palm oil seedling sources of Greenhouse Gas (GHG) emissions derived from the use of diesel fuel, NPK fertilizer, pesticides, and fungicides. Total emissions of Greenhouse Gases (GHG) is 0.50685 kg CO2 eq / seed. Diesel fuel became the biggest emissions is 0,332 kg CO2 eq / seed or 65.5 % and emissions from the use of NPK fertilizers is 0.1703 kg CO2 eq / seed or 33.6 % of total Greenhouse Gas ( GHG ) emissions in palm oil seedling.